Wearable Cameras in Health: The State of the Art and Future Possibilities (editorial) - Doherty, Aiden R.; Hodges, Steve; King, Abby C.; Smeaton, Alan F.; Berry, Emma; Moulin, Chris J.A.; Lindley, Siân; Kelly, Paul; Foster, Charlie (American Journal of Preventive Medicine, 2013)
Wearable cameras in health: The state of the art and future possibilities (editorial).